Silencing dissent: detection avoidance in extraterritorial targeted killings - Chaussée, Anna (Cases on forensic and criminological science for criminal detection and avoidance, 2024)
Forensic science deals with material traces of criminal activities and the attempts made to evade or delay detection. Detection avoidance behaviours require regular reappraisal in light of technological innovations, novel criminal cases, and theoretical and legal advancements. Apparent detection avoidant and concealment behaviours are contextualised within their established theoretical frameworks, particularly in the study of decision-making. It does so through the examination of the assassination of Khashoggi in 2018. Discussions go beyond the established explanations of detection avoidance by revealing attitudes towards material evidence, which cannot be explained adequately through RCT and 'forensic awareness' alone. Recognising detection avoidance strategies have obvious implications for forensic intelligence and as new perspectives emerge, it offers potentially valuable insights for those investigating human rights violations.